SOSIALISASI PERAN PEMERINTAH DESA TERHADAP PENGEMBANGAN POTENSI DESA DI DESA BANGKA KANTAR , KECAMATAN BORONG , MANGGARI TIMUR - Na'u, Sandriani; Koni, Maria Melania; Luge, Dili; Ola, Urbanus; Yanto, Marianus Diaz (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2025)
The Village Government is the government at the village level, which is responsible for organizing government, implementing development, fostering community development, and empowering communities in the village area. The purpose of implementing this socialization activity is to increase the understanding of the village government and community in developing the village's potential in Bangka Kantar Village, Borong District, East Manggarai. The socialization material includes: understanding the village government, the role of the village government, village potential, and the benefits of developing village potential. This implementation method is carried out through observation, coordination and implementation of activities. Participants involved in this activity are village officials and the community of Bangka Kantar Village, Borong District, East Manggarai. The results of the activity are expected to provide education to the village government and community, so that they can develop the potential of the village, so that they can increase village income and meet economic needs in households. Improving the Understanding of Village Government can be done by: Understanding the Duties and Functions of Village Government, Introduction and Development of Village Potential, Awareness of the Importance of Participation and Transparency, Strengthening Human Resources of the Village Apparatus